Peningkatan Keterampilan Membaca Pemahaman dengan Menggunakan Metode Generating Interacting Schemata and Text (GIST) di Sekolah Dasar - Rahmi, Yulia; Taufik, Taufina; mayarnimar, mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The research aimed at describe the improvement of comprehension reading skill by Using Generating Interacting Schemata and Text (GIST) Method in Grade IV of SD Negeri 13 Pasar Kambang Kecamatan Lengayang Regency of South Pesisir. Research subjects were teachers (practitioners) and 20 students. The average value of the class at the pre-cycle stage of cycle I 65.00 (enough) in cycle II increases to 75.00 (B), the stage when reading cycle I 68.00 (enough) in cycle II increases to 79.00 (B) , Stage pascabaca (65.00) in cycle II increased to 74.00 (B). Keywords: Reading comprehension skills, GIST methods, research results